Do profit-and-loss sharing and regional growth buffer credit risk in Islamic rural banks? - Nisa, Chaerani; Ichwani, Tia; kurniawati, Dewi (Faculty of Economics, Universitas Islam Indonesia, 2026)
Purpose – This study investigates how credit risk, profit-and-loss sharing (PLS) financing, and regional economic growth shape the profitability of Islamic rural banks in Indonesia and whether PLS portfolios and local conditions buffer the adverse effect of non-performing financing (NPF) on profitability through a moderating effect.Methodology – The analysis uses a balanced panel of 135 Islamic Rural Banks (IRBs) for 2019–2024, combining bank-level data with Gross Regional Domestic Product (GRDP) per capita growth. Fixed-effects panel regressions with two- and three-way interactions between NPF, PLS measures (total PLS, mudharabah, musharakah), and regional growth were estimated, controlling for size, capital adequacy, efficiency, funding structure, and time effects.Findings – The results demonstrate a robust negative association between non-performing financing (NPF) and return on assets (ROA). Mudharabah-based profit-and-loss sharing (PLS), rather than aggregate PLS or Musharakah alone, attenuates the impact of NPF. Similarly, higher regional growth weakens the marginal effect of credit risk. A negative and significant triple interaction indicates that Mudharabah intensity and favorable regional growth act as substitutes rather than complements, with the strongest mitigation of the NPF effect observed at low to moderate levels of both variables.Implications – The evidence suggests that IRB managers and regulators should calibrate PLS portfolios for regional macroeconomic conditions. Understanding local growth environments can guide the PLS configurations that are most appropriate for promotion within supervisory areas.Originality – This study is among the first to jointly examine the roles of PLS contract composition and regional economic growth in the credit-risk–profitability nexus of IRBs, showing how risk-sharing finance and local business cycles interact in shaping Islamic bank performance.